ANALISIS PENERAPAN STANDAR AKUNTANSI PEMERINTAHAN NO. 7 TAHUN 2010 TERHADAP PENCATATAN ASET TETAP DI PEMERINTAH KOTA SERANG PROVINSI BANTEN - Aditya, Deny; Khoirunnisa, Dini; Uzliawati, Lia (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2024)
Fixed assets refer to tangible assets that provide benefits for more than twelve months or at least one fiscal year and are utilized in operational activities within an entity. The objective of this study is to examine the similarities in the recording fixed assets at the Regional Agency for Financial Management and Savings (BPKAD) of Serang City, Banten Province, in alignment with the established Government Accounting Standards. The research employs a qualitative method, specifically utilizing a comparative analysis approach. The comparison involves assessing data from the previous year's research objects and examining the application of accounting to fixed assets in BPKAD Serang City based on Government Accounting Standards No. 7 of 2010. The findings indicate that the accounting treatment for fixed assets aligns with Government Accounting Standards Regulation No. 7 of 2010. Recognition, calculation, settlement, elimination, and the reduction in economic value are consistent with the SAP Policy No. 7 of 2010.